Cervical intradural extramedullay vascular schwannoma in a thirty eight year old male - Singhal, Shipra; Zaheer, Sufian; Arora, Rashmi (International Surgery Journal, 2019)
Schwannomas are benign peripheral nerve sheet tumours that may arise almost anywhere in the body but are commonly seen in the head, neck region and in the extremities. They may be associated with variable clinical presentations depending on their location. The peripheral nerves are closely related to vascular tissues morphologically and physiologically and therefore schwannomas may be associated with vascular changes like vascular hyperplasia and vascular dilation. Here authors represent one such case where a 38-year-old patient presented with a cervical swelling which on histopathology was diagnosed as vascular schwannoma.